Mastrevirus Rep and RepA Proteins Suppress de novo Transcriptional Gene Silencing - Kikyo Watanabe (MDPI AG, 2021)
Transcriptional gene silencing (TGS) in plants is a defense mechanism against DNA virus infection. The genomes of viruses in the Geminiviridae family encode several TGS suppressors. In this study, we induced de novo TGS against the transgenic GFP gene encoding green fluorescent protein by expressing a hairpin-shaped self-complementary RNA corresponding to the enhancer region of the 35S promoter (hpE35S). In addition, we examined the TGS suppression activity of proteins encoded in the genome of Tobacco yellow dwarf virus (TYDV, genus Mastrevirus). The results show that the replication-associated protein (Rep) and RepA encoded by TYDV have TGS suppressor activity and lead to decreased accumulation of 24-nt siRNAs. These results suggest that Rep and RepA can block the steps before the loading of siRNAs into Argonaute (AGO) proteins. This is the first report of TGS suppressors in the genus Mastrevirus.